Retracted: Long non‐coding RNA NORAD promotes the occurrence and development of non‐small cell lung cancer by adsorbing MiR‐656‐3p. Issue 8 (17th June 2019) - Chen, Tianyu; Qin, Shaoyun; Gu, Yinan; Pan, Huaqin; Bian, Dachen
Abstract: Background: To explore the role of non‐coding RNA activated by DNA damage ( NORAD ), a long non‐coding ribonucleic acid (lncRNA), in non‐small cell lung cancer (NSCLC) and its possible mechanism. Methods: Quantitative real‐time polymerase chain reaction was adopted for the detection of the expression levels of NORAD, micro RNA (miR)‐656‐3p, and AKT serine/threonine kinase 1 ( AKT1 ). The effects of NORAD, miR‐656‐3p, and AKT1 on cell proliferation and migration were examined through the Cell Counting Kit‐8 (CCK‐8) and Transwell assay. Subsequently, the binding relationships between miR‐656‐3p and AKT1 and between miR‐656‐3p and NORAD were verified by dual‐luciferase reporter gene assay. Finally, the potential mechanisms of action of NORAD and miR‐656‐3p were explored through the torsion experiment. Results: The lncRNA NORAD expression level in NSCLC patients was notably higher than that in people in control group, that in patients with metastasis was higher than that in patients without metastasis, and that in patients with NSCLC in stage III‐IV was significantly higher than that in patients with NSCLC in stage I‐II. Elevation of NORAD stimulated the proliferation and migration of NSCLC A549/H460 cells. According to the reporter gene assay, NORAD could bind to miR‐656‐3p. Besides, miR‐656‐3p was significantly under‐expressed in cancer tissues of patients with NSCLC, and overexpression of miR‐656‐3p could block the proliferation and migration of A549/H460 cells and reversed promotion on cell proliferation and migration by NORAD . Furthermore, the reporter gene assay revealed that the overexpression of AKT1, a miR‐656‐3p target gene, could reverse miR‐656‐3p's inhibitory effect on the proliferation and migration of A549/H460 cells. Conclusion: LncRNA NORAD is capable of promoting the proliferation and migration of NSCLC cells, and its mechanism may be that it increases the AKT1 expression by adsorbing miR‐656‐3p. Abstract : The lncRNA NORAD expression level in NSCLC patients was notably higher than that in people in control group, that in patients with metastasis was higher than that in patients without metastasis, and that in patients with NSCLC in stage III‐IV was significantly higher than that in patients with NSCLC in stage I‐II. Here, we reported that long non‐coding RNA NORAD may sponge miR‐656‐3p, as a competing endogenous RNA (ceRNA), to regulate AKT1 expression, exerting functional roles in NSCLC.